Economic mechanism of the nature management: institutional soil and instrumental methodological providing - Medynska, N. (Land Management, Cadastre and Land Monitoring, 2022)
It is deduced that the economic mechanism of nature management operates the insufficient set of methods, instruments and levers that give an opportunity to promote the complexity of the economic mastering of nature resource potential and strengthen the effectiveness of influence of the sphere of nature management on the rates of socio-economic presentation. Reasonably, that for the forming of modern economic mechanisms of nature management there is the necessity of the creation of institutional soil that will envisage installation in regulatory nature protection architectonics of new institutes-rules able to provide more effective bringing in of natural raw material and ecosystem services in market turnover. It is set that the instrumental methodological providing of economic mechanism of nature management must embrace the wide spectrum of methods, instruments and levers that will give an opportunity to provide budgetary-tax and financial credit influence on the maximum amount of the operations related to the exception of material substance of natural raw material and the usage of raw immaterial usefulness of nature complexes. Researches showed that in a modern economic mechanism nature management must present a wide spectrum of financially economic and administrative-economic methods. Financially economic methods embrace: evaluation, account, programming, planning, prognostication, taxation, budgetary financing, investing, insurance, crediting. To the list of administrative economic methods belong: licensing, examination, certification, regulation, standardization, monitoring, cadaster, limiting, and setting of norms. It is set that the modern economic mechanism of nature management must embrace budgetary, tax, custom, credit, hypothec-mortgage, fund, investment, insurance instruments, and also instruments that are based on realization of agreements of publicly-private partnership. Reasonably, that in the structure of economic mechanism of nature management two types of levers are distinguished: financially economic stimuli (tax deduction, favorable credits, reliefs from duty, price discounts/raise, cross subsidizing, dating) and financially economic approvals (fines, compensations, indemnifications, financial limitations, and budgetary limits). Key words: economic mechanism of nature management, institutional soil, methods, instruments, levers, public budgets.